2016
DOI: 10.1002/adfm.201504217
|View full text |Cite
|
Sign up to set email alerts
|

Penta‐Twinned Copper Nanorods: Facile Synthesis via Seed‐Mediated Growth and Their Tunable Plasmonic Properties

Abstract: We report the use of seed-mediated growth as a simple and versatile approach to the synthesis of penta-twinned Cu nanorods with uniform diameters and controllable aspect ratios. The success of this approach relies on our recently demonstrated synthesis of Pd decahedra as uniform samples, together with tightly controlled sizes in the range of 6-20 nm. When employed as a seed, the Pd decahedron can direct the heterogeneous nucleation and growth of Cu along the five-fold axis to produce a nanorod with a uniform d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
137
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 117 publications
(143 citation statements)
references
References 54 publications
(82 reference statements)
3
137
0
3
Order By: Relevance
“…The asymmetric growth pattern can be likely attributed to the large (7.1%) lattice mismatch between Cu and Pd. This observation was in agreement with previous reports on the synthesis of Pd@Cu core‐shell nanocubes and Pd−Cu penta‐twinned nanorods . When the reaction time was extended to 75 min, the deposited Cu atoms were able to diffuse to the other basal plane of a nanoplate.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The asymmetric growth pattern can be likely attributed to the large (7.1%) lattice mismatch between Cu and Pd. This observation was in agreement with previous reports on the synthesis of Pd@Cu core‐shell nanocubes and Pd−Cu penta‐twinned nanorods . When the reaction time was extended to 75 min, the deposited Cu atoms were able to diffuse to the other basal plane of a nanoplate.…”
Section: Resultssupporting
confidence: 92%
“…Two previous reports in our group found that the deposition of Cu atoms on Pd seeds varied significantly when the Pd seeds were changed from single-crystal cubes to multiply twinned decahedra. [13,14] Under the same reaction condition involving capping agents towards the Cu {100} facets, single-crystal Pd@Cu nanocubes and penta-twinned Cu nanorods were obtained when Pd cubes and decahedra were applied as the seeds, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[131] As illustrated in Figure 14 a, Au nanorods could be synthesized from decahedral Au seeds in the presence of Ag + ions. [85] Thekey is to slow down the reduction rate of the metal precursor through the formation of stable complexes,astrategy widely used to derive kinetically controlled structures. Theg rowth appeared to be initiated from both sides of the decahedral seed in asymmetric fashion.…”
Section: Symmetry Breaking or Reductionmentioning
confidence: 99%
“…Die zwei am häufigsten beobachteten mehrfach verzwillingten Keime weisen eine dekaedrische oder isokaedrische Form auf. Der hauptsächliche Sinn des Einsatzes mehrfach verzwillingter Keime für das Nanokristallwachstum ist der Zugang zu hoch anisotropen Strukturen, wie pentagonalen Nanostäbchen oder Nanodrähten, die aus einem uniaxialen Wachstum entlang der Fünffachachse dekaedrischer Keime herrühren können, ebenso wie zu Nanosternen oder –pentagrammen, die über ein dornenartiges Wachstum entlang der seitlichen Richtungen dekaedrischer Keime erhalten wurden . Diese Wachstumsprozesse werden durch eine inhomogene Verteilung von Spannungen und Zwillingsdefekten angetrieben.…”
Section: Klassifizierung Verschiedener Keimtypenunclassified
“…Den Autoren zufolge resultiert das 1D-Wachstum aus der Kombination der dekaedrischen Struktur sowie einer energetischen Differenzierung der Ebenen und Spitzen durch eine bevorzugte Unterpotentialabscheidung von Ag.I nn euen Untersuchungen wurde gefunden, dass das Wachstum auf eine der beiden Seiten eines dekaedrischen Pd-Keims beschränkt werden konnte,w odurch sich ein fünffach verzwillingtes Nanostäbchen aus Ag oder Cu bildete. [85] Der Schlüssel hierfüri st die Verlangsamung der Metallvorstufenreduktion durch Bildung stabiler Komplexe,e ine Strategie,d ie zur Herstellung kinetisch kontrollierter Strukturen weit verbreitet ist. [133] Asymmetrisches Wachstum kann auch bei Systemen erreicht werden, bei denen sowohl eine langsame Abscheidung als auch eine langsame Diffusion stattfinden.…”
Section: Die Rolle Der Oberflächendiffusionunclassified